2018
DOI: 10.3168/jds.2017-13164
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of a single dose of oral calcium based on postpartum plasma calcium concentration in Holstein cows

Abstract: Our objectives were to determine (1) the effect of a single dose of an oral Ca bolus within 24 h after parturition on plasma Ca concentration, (2) the response of primiparous (PP) and multiparous (MP) cows to this supplementation strategy, and (3) differential responses based on plasma Ca at enrollment. For objective 1, cows from 1 commercial dairy in New York State were enrolled within 19 h after parturition (mean ± standard deviation = 8.3 ± 5.3 h) and randomized within parity group (first, second, and ≥thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 31 publications
3
39
0
2
Order By: Relevance
“…However, the results presented here are not affected by the lack of disease information. Although peripartum disease may influence the evaluated outcomes, previous research has shown that diseases such as retained placenta, metritis, displaced abomasum, and mastitis are affected by oral calcium supplementation (Leno et al, 2018), and therefore, even if the information was available, it should not be considered as a covariate in the statistical models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results presented here are not affected by the lack of disease information. Although peripartum disease may influence the evaluated outcomes, previous research has shown that diseases such as retained placenta, metritis, displaced abomasum, and mastitis are affected by oral calcium supplementation (Leno et al, 2018), and therefore, even if the information was available, it should not be considered as a covariate in the statistical models.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research conducted to assess long-term implications of postpartum oral calcium supplementation on Holstein cows observed minimal treatment effects at a group level, and suggests that productive and health responses to oral calcium supplementation are conditional to cow-level factors (parity, productive potential, gestation length, dry period length, and locomotion score), which also influence the direction of that response (Oetzel and Miller, 2012;Martinez et al, 2016b;Leno et al, 2018). Additionally, cow-level factors have also been associated with increased risk of hypocalcemia (Roche and Berry, 2006;Neves et al, 2017;Valldecabres et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Jahani-Moghadam et al (2018) reported that oral Calcium bolus administration increased concentrations of calcium in serum on Day 2 post-partum in Holstein dairy cows, and increased first service conception rates, in cows fed a diet with a positive DCAD prior to calving compared to cows that received no oral Ca bolus supplementation. It is important emphasize that use of a single dose of calcium 24 h following parturition was reduced several risks, including retention placenta risk, mastitis, heart disease risk and displaced abomasum in multiparous cows (Leno et al 2018). Thus, treatment with oral calcium can be considered an approach to prevent not only hypocalcemia but also other disorders of dairy cows during the post-partum period.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy cows, the level of calcium in blood does not change, but there is an increase in milk productivity. In cows with initially reduced levels of total calcium in blood, it increases and improves the general condition [15,16].…”
Section: Introductionmentioning
confidence: 99%